Immediate impact of rapid maxillary expansion on upper airway dimensions and on the quality of life of mouth breathers - Edna Namiko Izuka; Murilo Fernando Neuppmann Feres; Shirley Shizue Nagata Pignatari (Dental Press Editora, 2015)
OBJECTIVE: To assess short-term tomographic changes in the upper airway dimensions and quality of life of mouth breathers after rapid maxillary expansion (RME). METHODS: A total of 25 mouth breathers with maxillary atresia and a mean age of 10.5 years old were assessed by means of cone-beam computed tomography (CBCT) and a standardized quality of life questionnaire answered by patients' parents/legal guardians before and immediately after rapid maxillary expansion. RESULTS: Rapid maxillary expansion resulted in similar and significant expansion in the width of anterior (2.8 mm, p < 0.001) and posterior nasal floor (2.8 mm, p < 0.001). Although nasopharynx and nasal cavities airway volumes significantly increased (+1646.1 mm3, p < 0.001), oropharynx volume increase was not statistically significant (+1450.6 mm3, p = 0.066). The results of the quality of life questionnaire indicated that soon after rapid maxillary expansion, patients' respiratory symptoms significantly decreased in relation to their initial respiratory conditions. CONCLUSIONS: It is suggested that RME produces significant dimensional increase in the nasal cavity and nasopharynx. Additionally, it also positively impacts the quality of life of mouth-breathing patients with maxillary atresia.